2001
DOI: 10.1212/wnl.57.8.1488
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil supplementation improves visual evoked potentials in children with phenylketonuria

Abstract: Visual evoked potentials (VEP) were measured in 36 patients with early-treated phenylketonuria (PKU; aged 1 to 11 years) and good metabolic control before and after supplementation with omega-3 long-chain polyunsaturated fatty acids (LC-PUFA) from fish oil. Patients with PKU had significantly longer P100 latencies than 22 age-matched control subjects. After 3 months of LC-PUFA supplementation, VEP latencies improved significantly in PKU patients but did not change in 12 untreated healthy children. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 12 publications
0
49
0
Order By: Relevance
“…Both children and adults with PKU have been found to have poor LC-PUFA status (Galli et al 1991, Sanjurjo et al 1994, Moseley et al 2002. The addition of DHA and AA (Agostoni et al 2000) or DHA and eicosapentaenoic acid by fish oil (Beblo et al 2001) to the diets of older children with PKU raises the levels of these fatty acids in plasma and improves the visual response of treated children. The effects of improved DHA status in infancy may be only transient, and, when infants are no longer fed on an LC-PUFA enriched formula, any improvement in neurodevelopment may be lost in later years.…”
Section: Discussionmentioning
confidence: 99%
“…Both children and adults with PKU have been found to have poor LC-PUFA status (Galli et al 1991, Sanjurjo et al 1994, Moseley et al 2002. The addition of DHA and AA (Agostoni et al 2000) or DHA and eicosapentaenoic acid by fish oil (Beblo et al 2001) to the diets of older children with PKU raises the levels of these fatty acids in plasma and improves the visual response of treated children. The effects of improved DHA status in infancy may be only transient, and, when infants are no longer fed on an LC-PUFA enriched formula, any improvement in neurodevelopment may be lost in later years.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond infancy, evidence linking EFA and LPCs with neurological benefits is limited to special population groups with very low dietary intakes of EPA and DHA, such as children with phenylketonuria [Beblo et al, 2001[Beblo et al, , 2007. These studies indicate that increasing DHA status with fish oil supplements is consistent with improvements in speed of information processing in the central nervous system as assessed by latencies of VEPs [Beblo et al, 2001], as well as marked improvements of coordination and fine motor skills [Beblo et al, 2007].…”
Section: Potential Outcomes For the Definition Of Dris For Lcps Of Nomentioning
confidence: 93%
“…Two studies (one of them an open label study) in treated PKU children showed that these children had prolonged visual evoked potentials compared to healthy controls. After supplementation with DHA, EPA (+ALA and AA) wave latency of visual evoked potentials decreased in both studies, indicating more rapid central nervous system information processing (Beblo et al, 2001). The open-label study also showed significant improvements of EPA+DHA supplementation on a test of motor function and coordination (Beblo et al, 2007).…”
Section: Evidence From Diseased Populationsmentioning
confidence: 80%